Conventions in the Foreign Exchange Market:Do they really explain Exchange Rate Dynamics? - Gabriele Di Filippo (FIW - Research Centre International Economics, 2010)
The present paper provides a new explanation for the dynamics of exchange rates based on conventions that prevail among market participants. The model relies on a two states Markov switching framework: a bull state and a bear state. In the bull state, agents are optimistic and put more weight on positive news about the domestic economy inducing an appreciation of the domestic currency. In the bear state, agents are pessimistic and overweight negative news associated to the domestic economy leading to a depreciation of the domestic currency. Results show that market switches between a bull state and a bear state explain the dynamics of the euro/dollar exchange rate between January 1995 and December 2008. Besides, the model highlights the life-cycle of conventions in the foreign exchange market and provides lessons for public authorities to reduce exchange rate volatility. Eventually, the model offers a solution to the exchange rate disconnection puzzle.
Keywords: G10; G12; F31; 330; Exchange Rate Dynamics; Convention Theory; Imperfect